2017
DOI: 10.1021/acs.chemmater.6b04090
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering for Extremely Large Grains in Explosively Crystallized TiO2 Films Grown by Low-Temperature Atomic Layer Deposition

Abstract: Functionality in thin films is closely linked with both the microstructure of the film as well as the innate nature of the thin film material. The engineering of microstructure, especially the grain size and its distribution in oxide thin films, is critical to designing functionalities targeting specific applications. However, the scope for manipulation of the microstructure of an oxide thin film is generally quite limited because of the lack of mobility of atoms at processing temperatures that are usually emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…The Raman data summarized in both Figures and , as well as those for SnO 2 /TiO x , also suggest that the crystallinity of the TiO x shell is dependent on the substrate, the shell thickness, and the annealing temperature utilized. The lower-temperature inflection point for a-TiO 2 /TiO x samples when compared to that for SnO 2 /TiO x is not unexpected, as the interfacial free energy between the a-TiO 2 core and a quasi-amorphous TiO x would be lower …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The Raman data summarized in both Figures and , as well as those for SnO 2 /TiO x , also suggest that the crystallinity of the TiO x shell is dependent on the substrate, the shell thickness, and the annealing temperature utilized. The lower-temperature inflection point for a-TiO 2 /TiO x samples when compared to that for SnO 2 /TiO x is not unexpected, as the interfacial free energy between the a-TiO 2 core and a quasi-amorphous TiO x would be lower …”
Section: Resultsmentioning
confidence: 86%
“…The lower-temperature inflection point for a-TiO 2 / TiO x samples when compared to that for SnO 2 /TiO x is not unexpected, as the interfacial free energy between the a-TiO 2 core and a quasi-amorphous TiO x would be lower. 101 Additional evidence of these different crystalline regimes as a function of temperature in a-TiO 2 /TiO x materials is apparent in HRTEM images. In all samples analyzed, the bulk nanocrystalline cores were highly crystalline, mainly displaying lattice fringe d-space values of 0.348 ± 0.002, 0.240 ± 0.004, and 0.188 ± 0.004 nm corresponding to the ( 101), (004), and However, after 20 ALD cycles, a-TiO 2 /TiO x -200 samples displayed thin disordered, quasi-amorphous edges with discontinuous lattice fringes and nanocrystals embedded in a quasi-amorphous matrix as the number of ALD cycles increased (i.e., as the pores become filled and nanoparticle interconnections increase) (Figure 5b).…”
Section: ■ Resultsmentioning
confidence: 96%
“…[ 10 ] It has been demonstrated that the nucleation of TiO 2 film is affected by the deposition conditions such as nature of the precursors, temperature, number of ALD cycles, as well as the nature and density of surfaces species of the substrate. [ 3,11 ] For example, our group has already studied the role of functional surface groups and defect sites on functionalized CNTs, which act as anchoring and nucleation sites for the initiation of film growth by ALD. [ 4a ] As a matter of fact, the nucleation behavior of ALD‐grown films was demonstrated to strongly correlate to the chemical and structural properties of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4a ] As a matter of fact, the nucleation behavior of ALD‐grown films was demonstrated to strongly correlate to the chemical and structural properties of the substrate. [ 11e,12 ] As a result, different substrates can alter the film properties and provide a simple strategy to tune its morphology and microstructure. There are principally two approaches to modify the surface of the substrate: one is the application of a chemical or physical treatment to the surface and the other is the deposition of a buffer layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation